Effects of Amoxicillin and Augmentin on Cystine-Glutamate Exchanger and Glutamate Transporter 1 Isoforms as well as Ethanol Intake in Alcohol-Preferring Rats - Hakami, Alqassem Y.; Hammad, Alaa M.; Sari, Youssef (Frontiers in Neuroscience, 2016)
Alcohol dependence is associated with alteration of glutamate transport and glutamate neurotransmission. Glutamate transporter 1 (GLT-1) is a major transporter that regulates the majority of extracellular glutamate concentration, which is also regulated by cystine-glutamate exchanger (xCT). Importantly, we recently reported that amoxicillin and Augmentin (amoxicillin/clavulanate) upreglulated GLT-1 expression in nucleus accumbens (NAc) and prefrontal cortex (PFC) as well as reduced ethanol consumption in male P rats. In this study, we examined the effects of amoxicillin and Augmentin on GLT-1 isoforms (GLT-1a and GLT-1b), xCT and glutamate/aspartate transporter (GLAST) expression in NAc and PFC as well as ethanol intake in male P rats. We found that both compounds significantly reduced ethanol intake, and increased GLT-1a, GLT-1b and xCT expression in NAc. However, only Augmentin increased GLT-1a, GLT-1b and xCT expression in PFC. There were no effects of these compounds on GLAST expression in NAc and PFC. These findings demonstrated that Augmentin and amoxicillin have the potential to upregulate GLT-1 isoforms and xCT expression, and consequently attenuate ethanol dependence.